The Bad Samaritans: The Elijah Motif in Luke 9.51-56. (March 2020) - Otten, Jeremy D.
The parallel between Jesus and Elijah in the account of the Samaritan village (Lk. 9.51-56; cf. 2 Kgs 1.1-16), though recognized for centuries, has almost always been seen as a negative one. Whether for reasons of typology, eschatology or as a polemic against violent judgment, scholars tend to argue that this passage distances Jesus from the OT prophet. This article examines the passage in light of the Elijah motif running throughout Luke–Acts, which is consistent in creating a positive link between Jesus and Elijah, especially in regard to compassion towards outsiders. In this light, the Lukan narrative presents Jesus' refusal to summon heavenly fire on the Samaritans as a truly Elijianic act. By contrast, the disciples, though attempting to emulate the Tishbite's actions, are ironically found to be in every way unlike Elijah.